DEVELOPMENT TRENDS OF GENERAL LIABILITY INSURANCE IN LITHUANIA - Augustytė, Ugnė; Jurevičienė, Daiva (Ekonomika, 2011)
The article deals with the situation of general liability insurance in Lithuania and its alteration, with an emphasis on the novelty of the topic. The essence of a particular insurance as well as the main insurable ranges in comparison with other types of insurance are reflected. The key problems related to general liability insurance in Lithuania are presented and discussed. A short overview of other countries’ experience is provided together with the nature of general liability insurance. The environment of general liability insurance and the key factors influencing it are discussed and highlighted. A qualitative and quantitative analysis of the development of general liability insurance market is made.